2009
DOI: 10.1016/j.regpep.2009.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin is dispensable for embryonic pancreatic islet development and differentiation

Abstract: Ghrelin is a peptide hormone that has been implicated in the regulation of food intake and energy homeostasis. Ghrelin is predominantly produced in the stomach, but is also expressed in many other tissues where its functions are not well characterized. In the rodent and human pancreas, ghrelin levels peak at late gestation and gradually decline postnatally. Several studies have suggested that ghrelin regulates beta cell function during embryonic development and in the adult. In addition, in a number of mouse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…However, ghrelin null mice showed no perturbation of islet cell populations and structure, indicating that ghrelin is not essential for normal islet formation. In addition, the elimination of ghrelin in Nkx2.2 K/K islets does not restore a-and b-cell populations, confirming that the event responsible for the loss of insulin-and glucagon-producing cells in Nkx2.2 null mice is not the upregulation of ghrelin (Hill et al 2009). …”
Section: Ag Uag and Ob Expression In The Endocrine Pancreasmentioning
confidence: 91%
“…However, ghrelin null mice showed no perturbation of islet cell populations and structure, indicating that ghrelin is not essential for normal islet formation. In addition, the elimination of ghrelin in Nkx2.2 K/K islets does not restore a-and b-cell populations, confirming that the event responsible for the loss of insulin-and glucagon-producing cells in Nkx2.2 null mice is not the upregulation of ghrelin (Hill et al 2009). …”
Section: Ag Uag and Ob Expression In The Endocrine Pancreasmentioning
confidence: 91%
“…In contrast, numbers of e cells were significantly increased in mice with deletions of Pax4, Pax6, or Nkx2.2, although this is at the expense of other islet cell types [67,68]. Interestingly, lineage-tracing studies demonstrated that e cells are not terminally differentiated endocrine cells, because in the adult mouse pancreas they can give rise to a, Ppy and, to a lesser extent, b cells [69].…”
Section: Ghrelin (E)-expressing Cellsmentioning
confidence: 98%
“…In the developing mouse and rat pancreas, ghrelin can be detected as early as embryonic day E9.5 and E15, respectively, and continues to be expressed throughout gestation, with levels peaking just before birth [Wierup et al, 2004;Jørgensen et al, 2007;Hill et al, 2009]. In the developing human pancreas, ghrelin cells are numerous from midgestation to the early postnatal period, and account for approximately 10% of all islet cells [Wierup et al, 2002].…”
Section: Similar Developmental Patterns Of Ghrelin-and Glucagon-exprementioning
confidence: 99%
“…However, several studies have shown the colocalization of ghrelin with either glucagon or insulin in both the human and rat pancreas [Date et al, 2002;Volante et al, 2002;Walia et al, 2009]. Emerging evidence suggests a lineage relationship among ghrelin-, insulin-and glucagon-producing cells in the developing pancreas [Hill et al, 2009]. The ghrelin-expressing cells appear to replace ␤ -and ␣ -cells in mice lacking the transcription factor Nkx2.2, Pax4 or Pax6.…”
Section: Similar Developmental Patterns Of Ghrelin-and Glucagon-exprementioning
confidence: 99%